THE INFLUENCE OF FOREIGN OWNERSHIP, INSTITUTIONAL OWNERSHIP, INDEPENDENT COMMISSIONERS, AND FINANCIAL DISTRESS TO STOCK PRICE WITH ACCOUNTING CONSERVATISM AS A MODERATION VARIABLE - Andi Firmansyah; Syarifuddin; Darmawati (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2023)
This study aims to analyze the influence of Foreign Ownership, Institutional Ownership, Independent Commissioners, Financial Distress using the disclosure of Accounting Conservatism as a moderating variable. Data collection obtained from the annual financial reports of Pharmacies listed on IDX 2017 – 2021 period, totaling 30 companies. The sampling technique used purposive sampling technique because the sample selection was based on the assessment some of the characteristics of the sample members which adjusted to the intentions of the researcher. using secondary data on the official IDX website (www.idx.co.id) and the official website of each company. The data analysis method used a special application of multiple linear regression analysis, namely using Moderated Regression Analysis (MRA) with a quantitative approach. The results of the study show that foreign ownership and independent commissioners do not affect stock prices. Institutional ownership and financial distress have a significant effect on stock prices. foreign ownership and independent commissioners influence share prices moderated by accounting conservatism. Institutional ownership and financial distress do not affect stock prices of pharmaceutical companies moderated by accounting conservatism